Development of an embedded system-based automatic timing reminder device for improving autoclave cooling period management - Yu Meng; Ping Gui; Shunlin Tan; Wei Zheng; Hao Wang (PLoS ONE, 2025)
Purpose The study was conducted with the aim of developing an automatic timing reminder device based on embedded systems to manage the cooling period of sterilized items autoclave in the Sterile Processing Department (SPD). The primary objective was to reduce the wet packs incidence rate and potential contamination risks by ensuring that sterilized items are allowed to cool for a minimum of 30 minutes before handling. Materials & methods The device, which utilizes the ATMEGA328 as the central control chip, incorporates a diffuse reflection type photoelectric sensor switch and encompasses modules for storage, power supply, speaker, display screen, real-time clock, and working indicator lights. It was programmed with Arduino 1.8.19 software to initiate timing upon sensor obstruction and emit reminders at predetermined intervals. Installed on a sterilizer cart using plastic cable ties, the device was tested over a 4-week period against a control group that relied on traditional methods for determining cooling time. The study monitored cooling time compliance rate, wet packs incidence rate, the frequency with which SPD technicians touched sterilized items, and technician satisfaction through a self-designed survey. Results The experimental group, using the timing reminder device, achieved a significantly higher cooling time compliance rate of 92.93% compared to the control group’s 72.92%. The wet packs incidence rate in the experimental group was markedly lower at 0.18%, contrasted with the control group’s 0.49%. Furthermore, the number of times SPD technicians touched sterilized items in the experimental group was significantly reduced compared to the control group. Additionally, the satisfaction score in the experimental group was notably higher than that of the control group. Conclusion The automatic timing reminder device, developed based on embedded systems technology, demonstrates good cost-effectiveness and high satisfaction among SPD technicians. It effectively standardizes the management process of autoclave. Therefore, the device holds significant potential for widespread application in other SPDs. Future research will further explore the potential applications of embedded systems in the healthcare field to expand its value in various medical procedures.